2009
DOI: 10.1108/14637150910987892
|View full text |Cite
|
Sign up to set email alerts
|

The role of BPR in the implementation of ERP systems

Abstract: PurposeThe role of business process re‐engineering (BPR) in implementing enterprise resource planning (ERP) systems is of paramount importance. A variety of approaches are used for such re‐engineering as the best‐fitting ERP solution can only give a maximum of 80 percent fit with the existing workflow of the organization in which ERP is being implemented. The aim of this paper is to focus on the issues involved.Design/methodology/approachThe paper presents some sample ERP installations to come out with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
0
28
0
4
Order By: Relevance
“…This study finds that BPR consideration affects "Information Quality", "User Satisfaction" and "Individual Impact". The role of BPR in ERP systems is crucial (Subramoniam et al, 2009). Companies should adopt BPR to adapt to ERP system, and should not modify the package to adapt to business process (Lambert, Jansen, and Splinter, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study finds that BPR consideration affects "Information Quality", "User Satisfaction" and "Individual Impact". The role of BPR in ERP systems is crucial (Subramoniam et al, 2009). Companies should adopt BPR to adapt to ERP system, and should not modify the package to adapt to business process (Lambert, Jansen, and Splinter, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Huq and Martin found the ERP-driven BPR can more easily design process change, and obtain a preview of project outcomes. Subramoniam, Tounsi, and Krishnankutty (2009) examined the role of BPR in implementing ERP systems and found that all organizations which implement ERP systems should select their own approach based on organizational needs and constraints. Furthermore, Sumner (1999) examined the relationship between critical success factors (CSFs) and ERP system performance, and identified the CSFs as management support, re-design of business processes, training and re-skilling, re-design of business processes, external consultants, management structure, discipline and standardization, effective communications, maintaining excellent staffing, and avoiding attempts at software modification.…”
Section: Bpr and Erp Systems Implementationmentioning
confidence: 99%
“…There is numerous literature available that after the implementation of ERP system the originations are able to increase their quality levels. Subramoniam and his colleagues examined the role of BPR in implementing ERP systems and found that all organizations which implement ERP systems should select their own approach based on organizational needs and constraints (Subramoniam, Tounsi, & Krishnankutty, 2009). ERP frameworks are mind boggling bits of programming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The motivation behind BPR is re-organizing or re-examining of business procedures and it should be possible with the backing of programming applications like Enterprise Resource Planning (ERP) (Grover, Jeong, Kettinger, & Teng, 2005). Subramoniam and his colleagues scrutinized the implementation of ERP and revealed that every organization should develop its own approach accordingly (Subramoniam, Tounsi, & Krishnankutty, 2009). Furthermore, recently Delvin Grant 2015, stressed that, all organizations who implement ERP system, they should select their own approach on the basis of organizational needs, it means modules that are selected, they should not be more than the needs of company that will be expensive and have no utility and not less than the requirements of company both will create failure of the ERP system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence BPR can be very useful in implementing ERP system in an organization. Similarly, ERP and e-commerce can be used as a constructive ground for BPR implementation (Subramoniam, Tounsi, & Krishnankutty, 2009). …”
Section: Searching For Common Groundmentioning
confidence: 99%